APLIKASI KEAMANAN PESAN (.TXT) MENGGUNAKAN METODE TRIPLE DES DAN METODE KOMBINASI LSB DAN BLUM-BLUM-SHUB - Derwin R Sina; Guido A Kiu; Bertha S Djahi; Emerensye S Y Pandie (Universitas Nusa Cendana, 2022)
Security is one of the important aspects of the process of exchanging information (messages). To prevent misuse or attacks by unauthorized parties (attackers) on private messages, the message must be secured. Several methods can be used to secure messages, one of which is by combining the Triple Data Encryption Standard (DES) cryptography method, Blum-Blum Shub (BBS) random number generator, and Least Significant Bit (LSB) steganography. In this study, the Triple DES cryptographic method is used to encrypt messages (embedded-message) with the extension .txt and the BBS random number generator method is used to determine the position of a random pixel to be inserted in the cover-image message. The LSB steganography method is used to perform the embedding process of the encrypted embedded-message at the pixel position resulting from the BBS random number generation process. The test results show that the system can extract embedded messages hidden in a stego-image with 100% accuracy. The maximum number of embedded-message characters that can be used in the test is 150 characters. The test also produces a stego-image that has an average Peak Signal to Noise Ratio (PSNR) value of 88.61, which means that the resulting stego-image has high quality (no significant quality degradation) and the presence of messages in the stego-image is getting harder to detect (imperceptibility).